FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA PROGRAM STUDI AKUNTANSI DALAM PEMILIHAN KARIR MENJADI AKUNTAN PUBLIK - Aryadi, I Nyoman Hendra; Ratnadi, Ni Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
The purpose of this study was to test empirically the factors that influence student interest in Career Selection to become a Public Accountant consisting of Artificial Intelligence knowledge, attitudes and parental influence with self-efficacy as a moderating variable. The population in this study were all students of the 2018 batch of Accounting Study Program, Faculty of Economics and Business, Udayana University, totaling 1316 students. Samples were taken using simple random sampling method. The number of samples was calculated using the Slovin formula with the number of samples in this study were 135 students. The data analysis technique of this research uses PLS (Partial Least Square). The results of the analysis prove that artificial intelligence knowledge, attitudes and parental influence have a positive and significant effect on student interest in choosing a career to become a Public Accountant, then self-efficacy is able to moderately strengthen the influence of artificial intelligence knowledge, attitudes and parental influence on the Interest of Accounting Study Program Students in Elections Career to become a Public Accountant